A closed-loop supply chain network considering consumer's low carbon preference and carbon tax under the cap-and-trade regulation - Cheng, Peiyue; Ji, Guoxin; Zhang, Guitao; Shi, Yangyan (Sustainable production and consumption, 2022)
This paper investigates the optimal strategies for an economic constrained closed-loop supply chain network. Manufacturers are classified into two categories namely low-emission manufacturers and high-emission manufacturers, and are subject to two greenhouse gas (GHG) emission control policies. Low-emission manufacturers are equipped with green production technologies to achieve ecological goals. All manufacturers are responsible in recycling and remanufacturing processes. New products and remanufactured products are homogeneous, and have the same sales price in the demand markets. Based on the variational inequality (VI) theory, we obtain the control equilibrium conditions of the non-cooperative game theory model for each firm. We further solve the model with the modified projection algorithm, and statically analyze and compare the influence of relevant parameters such as carbon quota, consumers’ low carbon preference and recovery rate on the network state through numerical examples. The results show that the GHG emission constraint may stimulate manufacturers to increase green technology investment level. Moreover, the introduction of reverse channel will promote resource recycling, but impair manufacturers’ profits. The promotion of consumer's environmental protection awareness has positive influence on the operation of supply chain network. In general, there is a conflict between economic goals and ecological ones. However, the developed model proves that economic goals and ecological ones can be realized consistently under certain conditions.